CONTRIBUTIONS OF SEARCH ENGINE OPTIMIZATION TECHNIQUES TO INFORMATION FINDABILITY - Camossi, Gustavo [UNESP]; Rodas, Cecilio Merlotti [UNESP] (Univ Federal Santa Catarina, 2023)
Objective: To demonstrate the contributions of Search Engine Optimization techniques to Information Findability in digital information environments. Method: Bibliographic research on Search Engine Optimization techniques and Information Findability in the field of Information Science was used as the methodology with a qualitative approach. Result: The results indicate that Search Engine Optimization techniques play a significant role in the capacity to find information on the Web, optimizing the attributes that favor the visibility of content in search results. Conclusions: It was concluded that, with the use of Search Engine Optimization techniques and technologies together with the attributes of Information Findability, it is possible not only to improve IF in digital environments but also to increase relevance and authority in the online environment, allowing users to easily find the information they need, thus contributing to the effectiveness of information systems.
Keywords: Search Engine Optimization; Information Findability; SEO